FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN SEJARAH DI SMAN 3 BUKIT BATU KABUPATEN BENGKALIS - Sriyani Sriyani; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: In the era of globalization, there must be changes in education. It cannot be denied that human development cannot be separated from education, both formal and non-formal education. The learning process which is the core of the formal education process at school in which there is an interaction between the various learning components. These components can be grouped into three main categories, namely teachers, content or learning materials, and students. History teachers at SMA N 3 Bukit Batu are more likely to use textbooks and blackboards for student learning, this is one of the factors that affect students' low interest in learning. The objectives of this study were (1) To determine the students' interest in learning class XI IPS in history subjects at SMA N 3 Bukit Batu, Bengkalis Regency. (2) To determine the factors that affect the students' interest in learning class XI IPS in history subjects at SMA N 3 Bukit Batu, Bengkalis Regency. In this study the authors used a qualitative method, which is an approach that focuses on the general principles that underlie the manifestation of a symptom that exists in human life or better known as patterns. The results of this study indicate that the students' interest in learning in class XI IPS is in the eye. History lessons at SMAN 3 Bukit Batu, Bengkalis Regency Need to be improved again. Factors that influence the learning interest of class XI IPS students at SMAN 3 Bukit Batu, namely the need for a sense of pleasure in history subjects, motivation and encouragement from teachers, parents, and friends as well as class cleanliness, school facilities such as facilities and infrastructure, and interests. students towards history subjects.Key Words: Factors, Influencing, Interest in Learning, History